Meta-analysis of microarray and RNAseq data reveal OsbZIP52 to mediate salt stress responses in sensitive, tolerant and halophyte rice varieties - Dipankor Chatterjee; Mohammad Umer Sharif Shohan; Nishat Tamanna; Zeba I. Seraj (CABI Agriculture and Bioscience)
Abstract The development of salt-tolerant rice has become urgent due to climate change and rising global rice consumption. A large-scale analysis using different but related platforms has become imperative to filter out candidate genes responsible for salinity tolerance and salinity stress-responsive pathways. Such genes can be used to find prospective candidate salt resistance genes in donor rice genotypes and transfer them to high-yielding rice varieties. We performed a meta-analysis to screen out candidate genes using stress-related three microarray and one RNASeq datasets from NCBI. As different genotypes of rice and different salinity stress conditions were considered in our analysis, the sensitivity of the results is expected to be multi-fold higher. Our analysis revealed the differentially expressed genes (DEGs) OsbZIP52 and OsLTP2.5 to be common between leaf and root tissues. These genes were further compared with those of the wild halophytic rice Oryza coarctata expression data in stress conditions to understand the significance of these genes. The OsbZIP52 gene homolog of Oryza coarctata was the only one found to be differentially expressed. The expression level of OsbZIP52 was quantified using RT-qPCR and observed downregulated expression in salt stress in root and leaf tissues of four rice cultivars (2 salt-tolerant and 2 salt-sensitive). Promoter and motif analysis revealed a high number of variations in promoter and motif regions of the gene in IR29 salt-sensitive rice. Expression correlation analysis and Gene Ontology study suggested that OsbZIP52 interacts with genes that are engaged in stress response and participate in stress-responsive pathways. Collectively this study increases our understanding of the differential gene expression in various stress conditions in root and leaf tissues. It also helped identify a critical regulatory transcription factor in assisting the plant in combating salinity stress.